2015
DOI: 10.1007/s00382-015-2768-x
|View full text |Cite
|
Sign up to set email alerts
|

Do the recent severe droughts in the Amazonia have the same period of length?

Abstract: We propose a new measure based on drought period length to assess the temporal difference between the recent two severe droughts of 2005 and 2010 in the Amazonia. The sensitivity of the measure is demonstrated by disclosing the distinct spatial responding mechanisms of the Northeastern and Southwestern Amazon (NA, SA) to the surrounding sea surface temperature (SST) variabilities. The Pacific and Atlantic oceans have different roles on the precipitation patterns in Amazonia. More specifically, the very dry per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Recent extreme climatic events in the region, such as droughts and floods, changes in the rainy and dry seasons, increased fire risk with associated their impacts on climate, health, and biodiversity are examples of what could happen in Amazonia as a consequence of climate change (Espinoza et al, 2011(Espinoza et al, , 2012aJiménez-Muñoz et al, 2013, 2016Gatti et al, 2014;Duffy et al, 2015;Erfanian et al, 2017;Aragão et al, 2018). Three "megadroughts" in 2005(Jiménez-Muñoz et al, 2016Marengo and Espinoza, 2016;Zou et al, 2016) were events classified at the time of their occurrence as "one-in-100 year event". Past mega-droughts were registered in 1925-1926, 1982-1983due to El Niño (Tomasella et al, 2011Marengo and Espinoza, 2016).…”
Section: Long-term Climate Trends In Amazoniamentioning
confidence: 99%
“…Recent extreme climatic events in the region, such as droughts and floods, changes in the rainy and dry seasons, increased fire risk with associated their impacts on climate, health, and biodiversity are examples of what could happen in Amazonia as a consequence of climate change (Espinoza et al, 2011(Espinoza et al, , 2012aJiménez-Muñoz et al, 2013, 2016Gatti et al, 2014;Duffy et al, 2015;Erfanian et al, 2017;Aragão et al, 2018). Three "megadroughts" in 2005(Jiménez-Muñoz et al, 2016Marengo and Espinoza, 2016;Zou et al, 2016) were events classified at the time of their occurrence as "one-in-100 year event". Past mega-droughts were registered in 1925-1926, 1982-1983due to El Niño (Tomasella et al, 2011Marengo and Espinoza, 2016).…”
Section: Long-term Climate Trends In Amazoniamentioning
confidence: 99%
“…Espinoza et al, 2011Espinoza et al, , 2013Casimiro et al, 2013). The northeastern Amazon precipitation is largely modulated by ENSO, and the southwestern part by the Atlantic SST (Aceituno, 1988;Tedeschi et al, 2013;Satyamurty et al, 2013a;Zou et al, 2016). However, the correlation between precipitation in the equatorial western Amazon and the Pacific and Atlantic SST is relatively weak (Enfield, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the El Niño-Southern Oscillation (ENSO) is an atmosphere-ocean coupled mode of climate variability in the tropical Pacific [Hoerling et al, 1997;McCabe and Dettinger, 1999;Yuan et al, 2015]. Zou et al [2015] showed that sea surface temperature variabilities in the tropical Pacific and Atlantic Oceans are of great importance in forming the climate conditions that drive interannual rainfall variations over the Amazon. In recent years, climate signals from the oceans, such as the ENSO, the North Atlantic Oscillation (NAO), and the Pacific Decadal Oscillation (PDO), have been treated as a source of climate predictability in dynamical forecasting for global and regional dry and wet conditions, because the oceans possess a large heat capacity and can act as a long-term memory for the climate system [Cayan et al, 1998;Barlow et al, 2001].…”
Section: Introductionmentioning
confidence: 99%